Effectiveness of a community health advisor colorectal cancer screening educational intervention on stool test completion in an African American primary care patient population: a pragmatic randomized controlled trial - John S. Luque; Gebre-Egziabher Kiros; Matthew A. Vargas; Askal Ali; Rima Tawk; Deloria R. Jackson; Sabrina L. Dickey; Cynthia M. Harris; Temple Robinson; Bessie Duncan; Jeanne’ Freeman; Clement K. Gwede; et al. (BMC Global and Public Health)
Abstract Background Colorectal cancer (CRC) disparities in incidence and mortality for African Americans compared to white Americans are explained by socioeconomic, behavioral, biological, and cultural factors in addition to lower screening rates and lower stage-specific survival. The behavioral clinical trial, “Test Up Now Education Program” (TUNE-UP) tested a community health advisor (CHA) intervention to increase stool-based screening in African American patients of community health centers (CHC) in Florida. Methods Participants who were not up to date with CRC screening were randomized to two study arms after completing a baseline survey. The two experimental arms were (1) an intervention group which received adapted “Screen to Save” CRC education, a tailored brochure, and CHA education; and (2) a control group which received the brochure only. Participants were surveyed at baseline, 3 months, and 12 months follow-up. The primary outcome was completion of the stool test within the last year, measured by self-report. The secondary outcomes were CRC knowledge, CRC perceived susceptibility, and CRC screening self-efficacy. For each arm, the proportion of participants who received CRC screening by 12 months was calculated. McNemar’s chi-square test was used to test changes in dichotomous outcomes related to CRC screening. For outcome variables measured on a continuous scale, a paired t-test was applied to compare changes in mean values. Generalized estimating equations (GEE) models were used to compare effects of the intervention on secondary outcomes, adjusting for covariates and confounding factors. Results At 12 months (n = 93), completion of the stool test increased significantly among participants in both study arms, showing no difference; 27 out of 45 (60%) participants in the intervention group and 28 out of 48 (58%) participants in the control group (p = 0.87).The intervention had a significant effect on the two secondary outcomes of CRC knowledge (p = 0.03) and CRC perceived susceptibility (p < 0.001) after adjusting for the covariates and confounders included in the model. Conclusions The trial demonstrated CHCs can increase CRC screening among African Americans who were not up to date in receiving recommended screening. Trial registration The clinical trial was registered on March 11, 2020 under the identifier https://clinicaltrials.gov/study/NCT04304001 .